EVALUASI PENAMBAHAN JUMLAH SKS (PRAKTIKUM) MATA KULIAH BIOTEKNOLOGI PADA PELAKSANAAN KURIKULUM BERBASIS KOMPETENSI TERHADAP HASIL BELAJAR MAHASISWA DI PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UNIVERSITAS RIAU - Imam Mahadi (Biogenesis, 2014)
Have implemented quality improvement research learning courses in Biotechnology Biology Education Guidance and Counseling Program at the University of Riau July to December 2013. Evaluation of student learning outcomes is done by comparing the student learning outcomes before and after implementation of the CBC. The samples were student results of 2005, 2006, 2007 ( before CBC ) and the class of 2008, 2009, 2010 ( after CBC ). Descriptive analysis of the data by comparing the cognitive and psychomotor aspects of learning outcomes and analyze the weaknesses in the implementation of the lecture and practicum students who have obtained. Results showed that without the use of practical learning outcomes for the class of 2005 earned an average value of 75.59, class of 2006, the average value of 73.71 and the class of 2007 with an average value of 76.72. Overall average value of 75.34 . While learning to use lab results to the class of 2008 with an average value of 72.32, for the class of 2009 with an average value of 76.66 and for the class of 2010 with an average value of 76.72. Overall average value of 74.94. Learning outcomes are assessed on the cognitive aspects of the implementation of learning theory after CBC ( 74.94 ) is lower than before using CBC ( 75.34 ), the psychomotor aspects of the implementation of the learning lab ( 76.33 ) is higher than the results of the study only assessed from the theory. Thus the addition of psychomotor aspects make students more easily understand and can apply the theory in practice, so as to improve learning outcomes.Keywords: Competency-Based Curriculum, Learning Outcomes, Theory and Practice of Biotechnology